Non-EFL Students’ Experience of Speaking English: A Project Based Learning in Making Video - Tira Nur Fitria; Uswatunnisa Uswatunnisa; Petrus Jacob Pattiasina (Al-Mudarris: Journal Of Education, 2022)
The objective of this research is to know the non-EFL students’ experience in making a project of English Speaking video as Project-Based Learning (PBL). This research is descriptive qualitative. The analysis shows that: students feel that speaking is a difficult skill in English, but they agree that the topic of the speaking project about ‘Introduction Myself & Others is “interesting”. In making an English project video, students make an Indonesian script then translate it into English, students read scripts when recording videos and almost do 5 times repetitions of making an English video project. The duration of making an English video project about more than 1 minute and 2 minutes duration.  During making an English project video, the students face difficulties, such as doing pause (pauses the message while thinking about what to say), doing filler (filling the gap in speaking with a certain voice (eeeeee, emmmmm, hmmm, and others), doing a mispronunciation/spelling error, doing a grammatical error, having a limited vocabulary, having trouble using accents in English, and having difficulty when expressing ideas. While, external students’ difficulties such as having mental problems, being easily distracted by their surroundings, having problems related to media (the audio/image is not clear), and having problems with lighting. By using video projects, students can know the vocabularies and how to read it in English, can know better English grammar, students can express ideas in speaking English, students feel courageous and confident in speaking English and they can improve their English speaking skills.